1983
DOI: 10.1093/bja/55.11.1095
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Midazolam and Diazepam for Sedation in Upper Gastrointestinal Endoscopy

Abstract: SUMMARYOne hundred and eighty-five patients were allocated at random to receive pethidine with diazepam (in an emulsion), or pethidine with miHuTnlam i. v. as sedation for upper gastrointestinal endpscopy. Sedation and conditions for examination were comparable and satisfactory in both groups. Midazolam produced more amnmia (P-<0.001), and scored higher in patients' opinion (P to <0.001); it was associated with a slightly greater frequency of venous sequelae, but the difference in thrombophlebitis was not stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 16 publications
3
15
1
Order By: Relevance
“…Recovery was similar in both the groups: Judged clinically, most patients had recovered, but their performance in Trieger testing significantly impaired at 4h after the administration of the drugs. This is consistent with published evidence for both the drugs [4,6]. Impaired cognitive response with diazepam and midazolam may be related to metabolites [7].…”
Section: Discussionsupporting
confidence: 92%
“…Recovery was similar in both the groups: Judged clinically, most patients had recovered, but their performance in Trieger testing significantly impaired at 4h after the administration of the drugs. This is consistent with published evidence for both the drugs [4,6]. Impaired cognitive response with diazepam and midazolam may be related to metabolites [7].…”
Section: Discussionsupporting
confidence: 92%
“…Psychomotor performance, measured using the Trieger test, was equally impaired by either drug for up to two hours after sedation. 17 Neither the present study nor any of the studies reviewed have shown a clear advantage in safety or more rapid recovery when midazolam is compared with diazepam. In two surveys 11,12 of endoscopic practice, patient morbidity was reported equally frequently with either drug.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies of its use for sedation during EGD have suggested that it is more potent, faster acting, and provides greater amnesia and patient acceptance of the procedure than diazepam [10][11][12][13][14][15][16]. However, experience with midazolam in children has been largely limited to use as an induction agent for gen eral anesthesia [17,18].…”
mentioning
confidence: 99%